ABDOMINAL MASSAGE UNTUK MENGATASI KONSTIPASI PASIEN DI INTENSIVE CARE UNIT (ICU): LITELATURE REVIEW: ABDOMINAL MASSAGE TO OVERCOME PATIENT CONSTIPATION IN THE INTENSIVE CARE UNIT (ICU): LITELATURE REVIEW - Sudjarwo, Eddi; Ramadhan, Muhammad Putra (Jurnal Keperawatan Terapan, 2022)
Abstract: Constipation is a side effect on the gastrointestinal system that often occurs in patients treated in the Intensive Care Unit (ICU). Constipation is a problem that has not been given much special attention. Abdominal massage is one of the complementary therapies that can increase the movement of the gastrointestinal system. The results obtained from the application of abdominal massage are a decrease in the incidence of constipation. The method used is an approach to 5 research journals on abdominal massage to reduce constipation in patients treated in the Intensive Care Unit (ICU). The journal obtained shows that abdominal massage therapy can overcome constipation problems. The journal results obtained also showed that there were improvements in several other gastrointestinal tract indicators such as gastric residual volume, abdominal circumference, abdominal tension, and others. There is one journal that can be used as one of the Evidence Based Nursing (EBN) in clinical services, especially in the intensive care unit (ICU). Keywords: constipation, abdominal massage, intensive care unit.